Beyond awareness: the binding of reflexive mechanisms with the conscious mind: a perspective from default space theory - Jerath, Ravinder; Beveridge, Connor (Frontiers in Human Neuroscience, 2024)
How do reflexes operate so quickly with so much multimodal information on the environment? How might unconscious processes help reveal the nature of consciousness? The Default Space Theory of Consciousness (DST) offers a novel way to interpret these questions by describing how sensory inputs, cognitive functions, emotional states, and unconscious processes are integrated by a single unified internal representation. Recent developments in neuroimaging and electrophysiology, such as fMRI, EEG, and MEG, have improved our knowledge of the brain mechanisms that underpin the conscious mind and have highlighted the importance of neural oscillations and sensory integration in its formation. In this article, we put forth a perspective on an underresearched relationship of reflexes with the dynamic character of consciousness and suggest that future research should focus on the interplay of the unconscious processes of reflexes and correlates of the contents of consciousness to better understand its nature. Existing research on the top-down cortical influence over the subcortical operations of reflexes is severely lacking. This top-down influence has been demonstrated, but how the complex multimodal model of the self and environment is encoded and utilized to produce quick and coordinated reflex responses is not understood. Integrating unconscious/subconscious reflexive mechanisms with models of consciousness may illuminate a boundary between or gradient among conscious and unconscious activity. This perspective in light of the DST’s framework may reveal future research avenues aimed at understanding the complexities and physical nature of consciousness.